Problem

Use the definition in Expression (3.13) to prove that V(aX + b) = σ2. σ2x [ Hint: With h...

Use the definition in Expression (3.13) to prove that V(aX + b) = σ2. σ2x [ Hint: With h(X) = aX + b, E[h(X)] = aµ = b where µ = E(X).]

Reference Expression (3.13

The variance of h(X) is the expected value of the squared difference between h(X) and its expected value:

When h(X) = aX + b, a linear function,

Substituting this into (3.13) gives a simple relationship between V[h(X)] and V(X):

Step-by-Step Solution

Request Professional Solution

Request Solution!

We need at least 10 more requests to produce the solution.

0 / 10 have requested this problem solution

The more requests, the faster the answer.

Request! (Login Required)


All students who have requested the solution will be notified once they are available.
Add your Solution
Textbook Solutions and Answers Search